PENGENDALIAN KUALITAS ATRIBUT KEMASAN MENGGUNAKAN METODE FAILURE MODE EFFECT ANALYSIS (FMEA)PADA PROSES PRODUKSI AIR MINUM DALAM KEMASAN - Anik Satria Dewi, Ni Wayan; Mulyani, Sri; Arnata, I Wayan (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2016)
The purpose of study: 1. determine the types of defects in the product packaging plastic cups 240 ml, 2. determine the factors that cause defectsin the product, 3. formulated alternative improvements to reduce the defect rate of the product. Research carried out by carrying out preliminary studies and literature, collection of data and then processed and analyzed. Data processing is done using: histogram, p-chart, fishbone diagram and Method Failure Mode Effect Analysis (FMEA). The data are analyzed to derive the value of the Risk Priority Number (RPN) to provide the highest proposed improvement alternative. The results showed that the types of defects are: leaking cup defects, dents glass defects, labeling defect, amount of volume defect and defect content of the product and disability amount to an  average of product defects 3.53% of the total production per month. Factors that cause disabilityif sorted by degree are: human, packaging materials, environment, methods, and machinery. Once the causes of defects is controlled decrease the number of defects with an average value of 2.4%of total production per month. Recommendations for improvement are given is to control all the processes in the packaging division, especially the checking process, because  the checking process has the highest RPN value with a value of 576 Keywords: Quality, Defect, Statistical Quality Control, FMEA
Keywords: 114